PENGARUH MODEL PROBLEM BASED LEARNING (PBL) TERHADAP MINAT BELAJAR SISWA DENGAN BANTUAN MEDIA VISUAL PADA TEMA CUACA DI KELAS III SD NEGERI 104280 PULAU GAMBAR - Eka Pratiwi, Dhiyanda; Sujarwo (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The objective of this research was to determine the improvement in student learning interest using visual media to prevent boredom during thematic learning on the weather theme, which includes Indonesian language and mathematics. This research used a quantitative approach with a one-group pretest-posttest design and employed the ProblemBased Learning (PBL) model. The data collection instruments were questionnaires and observations. Based on inferential statistical analysis using the t-test formula, the calculated t-value was 0.052%. With a frequency (df) of 25-1=24, at a significance level of 0.05%, the ttable value was 0.025. Since the t-calculated value > t-table value at the 0.05 significance level, the null hypothesis (H₀) was rejected, and the alternative hypothesis (Hₐ) was accepted. This indicates that there is an effect of implementing the Problem-Based Learning (PBL) model on student learning interest with the help of visual media on the weather theme at SD Negeri 104280 Pulau Gambar.